Peripapillary vascular changes in radiation optic neuropathy: an optical coherence tomography angiography grading. Issue 9 (17th January 2018) - Parrozzani, Raffaele; Frizziero, Luisa; Londei, Davide; Trainiti, Sara; Modugno, Rocco Luigi; Leonardi, Francesca; Pulze, Serena; Miglionico, Giacomo; Pilotto, Elisabetta; Midena, Edoardo
Abstract : Aims: To investigate peripapillary vascular changes secondary to radiation optic neuropathy (RON) using optical coherence tomography angiography (OCT-A) and to propose a clinical grading of RON based on OCT-A findings. Methods: Thirty-four patients affected by RON were consecutively included. Each patient underwent best corrected visual acuity measurement (ETDRS score) and OCT-A (Nidek RS-3000 Advance device, Nidek, Gamagori, Japan). The radial peripapillary capillary plexus (RPCP) and the entire peripapillary capillary bed (EPCB) were analysed. Quantitative analysis of the OCT-A images was performed using open-source available ImageJ software (National Institutes of Health, Bethesda, Maryland, USA). Qualitative analysis based on the proposed clinical grading (Grades 0–4) was also performed by two masked graders. Results: RON clinical (qualitative) classification based on RPCP correlated with the quantitative RPCP perfusion analysis (P=0.0001). RON clinical classification based on RPCP statistically correlated with ETDRS score (P=0.001). RON clinical classification based on EPCB also correlated with the quantitative EPCB perfusion analysis and ETDRS score (P=0.02 and P=0.01, respectively). Compared with the clinical classification based on EPCB, the qualitative classification based on RPCP reached a higher intergrader agreement (0.96 and 0.86, respectively). Conclusion: OCT-A can be used to detect RPCP abnormalities and to clinically classify RON with a high interexaminer agreement. The proposed clinical classification is supported by the quantitative analysis based on the use of specific images elaboration techniques and correlates with visual acuity of the examined eyes.